Cellulose-based hydrogel meeting 3D printing and sensing performance as well as preparation method and application of cellulose-based hydrogel

By pretreating cellulose with alkalization and combining with a metal salt solution with a specific ratio, a cellulose-based hydrogel with excellent freezing resistance and high conductivity under low temperature environments was prepared, which solved the problem of insufficient freezing resistance at low temperatures, and expanded its application in flexible sensors and wearable electronic devices.

CN119751986AActive Publication Date: 2025-04-04SAIC GM WULING AUTOMOBILE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411761487.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-04
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing cellulose-based hydrogels have insufficient anti-freeze performance in low temperature environments, resulting in a significant decline in mechanical properties, limiting their application in flexible sensors and wearable electronic devices.

Method used

A cellulose-based hydrogel containing zinc salt, lithium salt, water and alkalized pretreated cellulose was prepared by alkalizing the cellulose and combining the proportion of the alkalized pretreated cellulose and metal salt solution of a specific content. The hydrogel has no crystallization behavior at temperatures as low as -80°C, and has excellent freezing resistance and high conductivity and mechanical properties.

Benefits of technology

It has achieved excellent freezing resistance and high conductivity and mechanical properties of cellulose-based hydrogels in low temperature environments, and broadened its application prospects in flexible sensors, wearable electronic devices and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751986A_ABST
    Figure CN119751986A_ABST
Patent Text Reader

Abstract

The invention relates to the fields of hydrogel 3D printing, flexible sensors and wearable electronic equipment, in particular to cellulose-based hydrogel meeting 3D printing and sensing performance as well as a preparation method and application of the cellulose-based hydrogel. The cellulose-based hydrogel contains zinc salt, lithium salt, water and cellulose subjected to alkalization pretreatment, in the cellulose-based hydrogel, the total mass of zinc salt, lithium salt and water is 100%, the content of the cellulose subjected to alkalization pretreatment is 1%-6%, the molar ratio of the total amount of the zinc salt and the lithium salt to the water is 1: (3-4), the molar ratio of the zinc salt to the lithium salt is 1: (0.4-2.4), and the molar weight of the zinc salt and the molar weight of the lithium salt are both based on the content of the zinc element and the content of the lithium element. According to the cellulose-based hydrogel and the preparation method thereof, the cellulose subjected to alkalization pretreatment is adopted, the ratio of the cellulose subjected to alkalization pretreatment and the metal salt solution (containing the zinc salt, the lithium salt and the water) with the specific content and the composition of the metal salt solution are combined, the cellulose-based hydrogel meeting the sensing and 3D printing performance is obtained, and the cellulose-based hydrogel has the better anti-freezing performance; the composite material has relatively high conductivity and relatively good mechanical properties, and an unexpected technical effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of hydrogel 3D printing, flexible sensors and wearable electronic devices, and in particular to a cellulose-based hydrogel meeting 3D printing and sensing performances, and a preparation method and application thereof. Background Art

[0002] Hydrogel is a three-dimensional hydrophilic or water-soluble polymer network system formed by certain chemical or physical crosslinking. It can absorb a large amount of water and maintain a certain soft material shape. It has the characteristics of high water content, excellent biocompatibility, good environmental sensitivity, good functional designability and structural controllability. However, traditional polymer hydrogels are not easy to degrade, lack biological functions, and their petrochemical raw materials cannot be regenerated in a short period of time.

[0003] The prior art points out that cellulose is a renewable resource and contains a large amount of hydroxyl groups, which can be used to prepare hydrogels. CN 109942838A discloses a method for preparing a cellulose conductive hydrogel that can be used for 3D printing, which includes preparing a mixed solution of ZnCl2 and CaCl2, adding cellulose, and dissolving it under the condition of 50℃ to 90℃ by magnetic stirring for 10min to 90min until it is completely dissolved to obtain a cellulose solution; adding water or a small molecule alcohol to the cellulose solution, and magnetically stirring it under the condition of 50℃ to 90℃ for 5min to 30min until it is uniform; degassing and cooling to obtain a cellulose conductive hydrogel. The cellulose hydrogel has certain advantages in terms of electrical conductivity, but its antifreeze performance has certain limitations. The mechanical properties of the hydrogel in a low temperature environment are significantly reduced. For example, the elongation at break of the gel at -20°C is only 80% of that at room temperature, and the elongation at break of the hydrogel at -60°C is only 54% of that at room temperature, indicating that under the conditions of -20°C and -60°C, the resulting hydrogel has undergone partial crystal freezing, which affects its performance and service life in a low temperature environment. Its antifreeze performance needs to be further improved, which limits its application in the fields of flexible sensors and electric vehicles. Its tensile strength at room temperature is also low (only 0.35MPa). Cellulose-based hydrogel is a soft material, and mechanical properties are an important factor affecting its application development. Improving its tensile strength can provide better deformability and shape memory performance in the field of flexible sensors, making it more flexible and durable. In the biomedical field, it can improve the delivery efficiency and tissue repair ability.

[0004] Therefore, how to provide a cellulose-based hydrogel with excellent antifreeze and mechanical properties on the basis of good electrical conductivity is a technical problem that needs to be solved at present. Summary of the invention

[0005] In response to the above technical problems, the present invention provides a cellulose-based hydrogel that meets 3D printing and sensing performance, and a preparation method and application thereof. The cellulose-based hydrogel of the present invention overcomes the disadvantage of being not frost-resistant in the prior art, has excellent antifreeze performance, and can be free of crystallization behavior at temperatures as low as -80°C. On the basis of having excellent antifreeze performance, the cellulose-based hydrogel of the present invention also has good electrical conductivity and mechanical properties.

[0006] The first aspect of the present invention is to provide a cellulose-based hydrogel, comprising zinc salt, lithium salt, water and alkali-pretreated cellulose; in the cellulose-based hydrogel, based on the total mass of zinc salt, lithium salt and water as 100%, the content of the alkali-pretreated cellulose is 1%-6%, the molar ratio of the total amount of zinc salt and lithium salt to water is 1:(3-4), the molar ratio of zinc salt to lithium salt is 1:(0.4-2.4), and the molar amounts of zinc salt and lithium salt are both calculated based on the content of zinc element and lithium element.

[0007] As mentioned above, the antifreeze performance of cellulose-based hydrogels in the prior art needs to be further improved. Cellulose is difficult to dissolve in general salt solutions. Even if it is dissolved, it is difficult to obtain a cellulose-based hydrogel with high conductivity, good mechanical properties, and higher antifreeze performance. The present invention uses alkalized pretreated cellulose, combined with a specific content of alkalized pretreated cellulose and a metal salt solution (containing the above-mentioned zinc salt, lithium salt and water) The ratio, as well as the composition of the metal salt solution, obtains a cellulose-based hydrogel that meets the sensing and 3D printing performance, and has better antifreeze performance, and has both high conductivity and good mechanical properties, and has achieved unexpected technical effects.

[0008] The inventors have studied and believe that the technical effects of the present invention are achieved because:

[0009] The present invention can refine and shorten the cellulose microfiber bundles by alkalizing the cellulose for pretreatment, so that the cellulose can be easily dissolved in the metal salt solution of the present invention;

[0010] By adjusting the cellulose content, it has good 3D printing performance;

[0011] By adjusting the ratio of metal salts (zinc salt, lithium salt), the dissolution of cellulose and good conductive sensing performance can be achieved. The metal cations first enter the cellulose network structure to swell, and then form coordination bonds with the cellulose hydroxyl groups. The hydrogen bonds inside and between cellulose molecules are destroyed, and finally it dissolves into a cellulose solution with transparent color and uniform texture.

[0012] If the zinc salt content is too high, the strength of the final cellulose-based conductive hydrogel will be weakened, and salt precipitation will easily occur at low temperatures. If the zinc salt content is too low, cellulose will be difficult to dissolve.

[0013] The strength and toughness of cellulose-based conductive hydrogels also increase with the increase of lithium salt content. This may be because the mechanical properties of cellulose-based conductive hydrogels depend to a certain extent on the coordination bonds formed between metal salt ions and cellulose molecules through chelation. When the content of zinc salt and lithium salt changes, the coordination balance between cellulose and metal salt ions is broken, and its mechanical properties also change accordingly.

[0014] The metal salt solvent system (i.e., metal salt solution) dissolves the cellulose obtained after the pretreatment of the present invention, and there are free ions in the cellulose-based conductive hydrogel system. The free ions can move in the three-dimensional network system of the cellulose-based conductive hydrogel, providing ion carriers for the conductivity of the cellulose-based hydrogel, thereby effectively improving the conductivity and sensing performance of the cellulose-based conductive hydrogel.

[0015] The present invention affects the rheological properties of cellulose by optimizing the ionized structure of cellulose and the solvent / dispersant system to meet the requirements of 3D printing, and constructs a cellulose-based conductive hydrogel material with a designable structure; on the basis of the aforementioned properties, the cellulose-based conductive hydrogel of the present invention has excellent antifreeze properties. The present invention improves the antifreeze and mechanical properties of cellulose-based hydrogels, making their application prospects broader.

[0016] According to the present invention, the cellulose-based hydrogel of the present invention contains zinc salt, lithium salt, water and alkali-pretreated cellulose; in the cellulose-based hydrogel, the total mass of zinc salt, lithium salt and water is 100%, the content of the alkali-pretreated cellulose is 1%-6%, the molar ratio of the total amount of zinc salt and lithium salt to water is 1:(3-4), the molar ratio of zinc salt to lithium salt is 1:(0.4-2.4), and the molar amount of zinc salt and lithium salt is calculated based on the content of zinc element and lithium element. The composition of the above-mentioned cellulose-based hydrogel can be calculated by the feed amount in the preparation method, and the composition of the cellulose-based hydrogel product can also be detected by the detection means of the prior art. For example, the water content can be detected by a moisture detector, the cellulose content can be detected by a cellulose analyzer, and the zinc salt and lithium salt content can be detected by atomic absorption spectroscopy.

[0017] According to some preferred embodiments of the present invention, in the cellulose-based hydrogel, based on the total mass of zinc salt, lithium salt and water as 100%, the content of the alkalized pretreated cellulose is 2%-5%, more preferably 3%-5%.

[0018] According to some preferred embodiments of the present invention, the molar ratio of the total amount of zinc salt and lithium salt to water is 1:(3-3.5).

[0019] According to some preferred embodiments of the present invention, the molar ratio of zinc salt to lithium salt is 1:(0.6-1.5), preferably 1:(0.8-1.2).

[0020] According to some preferred embodiments of the present invention, the zinc salt is selected from at least one of Zn(NO3)2, ZnBr2, and ZnSO4.

[0021] According to some preferred embodiments of the present invention, the lithium salt is selected from at least one of LiBr, LiCl, and Li2SO4.

[0022] According to some preferred embodiments of the present invention, the method for preparing the alkalized pretreated cellulose comprises:

[0023] The cellulose is alkalized in an alkali solution, washed to neutrality, dissolved in a mixed solvent, and freeze-dried to obtain alkalized pretreated cellulose.

[0024] According to some more preferred embodiments of the present invention, in the method for preparing the alkalized pretreated cellulose:

[0025] The cellulose is selected from at least one of cotton pulp cellulose, hemp fiber, and lignin fiber; and / or,

[0026] The base in the alkaline solution is selected from at least one of a weak base and a strong base, preferably the weak base is selected from at least one of Na2CO3 and K2CO3, preferably the strong base is selected from at least one of KOH and NaOH; and / or,

[0027] The mass ratio of alkali to water in the alkaline solution is 1:(15-25); and / or,

[0028] The amount of the alkaline solution used is 80-120 mL relative to 1 g of cellulose.

[0029] According to some preferred embodiments of the present invention, in the method for preparing the alkalized pretreated cellulose:

[0030] The conditions of the alkalization treatment include: a temperature of 20-30° C. and a time of 1-3 h, and / or, the pretreatment is carried out under mixing conditions, preferably using a high-speed homogenizer for stirring; and / or,

[0031] The method of washing to neutrality is: repeatedly washing the cellulose obtained after pretreatment with water until it becomes neutral; and / or,

[0032] The mixed solvent is a mixed solution of alcohol and water, and preferably the alcohol is selected from at least one of anhydrous ethanol and propylene glycol; and / or the volume ratio of alcohol to water is (2:8) to (4:6).

[0033] According to the present invention, the water may be conventional experimental water, including but not limited to deionized water.

[0034] According to the present invention, preferably, the freeze-drying process is carried out in a freeze dryer.

[0035] The second aspect of the present invention is to provide a method for preparing the cellulose-based hydrogel according to the first aspect, comprising:

[0036] The alkalized pretreated cellulose is dissolved in an aqueous solution containing zinc salt and lithium salt to obtain a cellulose-based hydrogel.

[0037] According to some preferred embodiments of the present invention, based on the total mass of zinc salt, lithium salt and water as 100%, the amount of the alkalized pretreated cellulose is 1%-6%, preferably 2%-5%, more preferably 3%-5%.

[0038] According to some preferred embodiments of the present invention, in the aqueous solution containing zinc salt and lithium salt:

[0039] The molar ratio of the total amount of zinc salt and lithium salt to water is 1:(3-4), preferably 1:(3-3.5); and / or the molar ratio of zinc salt to lithium salt is 1:(0.4-2.4), preferably 1:(0.6-1.5), more preferably 1:(0.8-1.2), and the molar amounts of zinc salt and lithium salt are both calculated based on the content of zinc element and lithium element.

[0040] According to some preferred embodiments of the present invention, the zinc salt is selected from at least one of Zn(NO3)2, ZnBr2, and ZnSO4.

[0041] According to some preferred embodiments of the present invention, the lithium salt is selected from at least one of LiBr, LiCl, and Li2SO4.

[0042] According to some preferred embodiments of the present invention, the dissolution conditions include: a temperature of 90-120° C., and / or a time of 3-5 hours; preferably, a temperature of 90-100° C., and / or a time of 3-4 hours. Under the preferred dissolution conditions, cellulose can be better dissolved without degrading cellulose.

[0043] According to the present invention, the process of dissolving cellulose is carried out under mixing conditions, and the mixing method can be conventional methods such as stirring, including but not limited to magnetic stirring.

[0044] According to some preferred embodiments of the present invention, the preparation method further comprises:

[0045] After dissolving the alkalized pretreated cellulose in an aqueous solution containing zinc salt and lithium salt to obtain a cellulose-based hydrogel, the cellulose-based hydrogel is injected into a container and then subjected to a degassing treatment. Preferably, the container is placed in a centrifuge for degassing.

[0046] According to the present invention, the preparation method further comprises the step of preparing an aqueous solution containing zinc salt and lithium salt according to the composition of raw materials, for example, directly mixing zinc salt, lithium salt and water, stirring until the salt is dissolved, and obtaining an aqueous solution containing zinc salt and lithium salt (also called metal salt solution). During the mixing process, in order to accelerate the dissolution rate, it can also be heated appropriately, for example, heated to 90-120° C.; it is also possible to first prepare a zinc salt aqueous solution and a lithium salt aqueous solution with a higher concentration, and then, according to the composition of the raw materials, take an appropriate zinc salt aqueous solution and a lithium salt aqueous solution and optionally add part of water to obtain an aqueous solution containing zinc salt and lithium salt.

[0047] The third aspect of the present invention is to provide an application of the cellulose-based hydrogel described in the first aspect or the cellulose-based hydrogel prepared by the preparation method described in the second aspect in the fields of 3D printing, flexible sensors, and wearable electronic devices.

[0048] According to some preferred embodiments of the present invention, when the cellulose-based hydrogel is used for 3D printing, the moving speed of the 3D printing nozzle is 80-130 mm / min; and / or the injection speed of the injection pump containing the cellulose-based hydrogel is 30-60 uL / min.

[0049] As for 3D printing, this is an existing technology. For example, you can first use CAD to model the target graphics, and then use Simply 3D slicing software to slice the model and import it into a 3D printer for printing. I will not go into details here.

[0050] The present invention prepares a cellulose-based conductive hydrogel. The cellulose molecular structure is rich in hydroxyl groups, which can form a large number of hydrogen bonds, cross-link to form a three-dimensional network structure, and form intermolecular interactions with the hydrogel, so that a green and environmentally friendly cellulose hydrogel with good degradability, biocompatibility, flexibility, and water absorption can be constructed, which has a wide range of application research in many fields such as biomedicine and flexible electronic devices.

[0051] Compared with traditional synthetic polymer hydrogels, cellulose-based hydrogels are non-toxic, degradable, biocompatible, environmentally friendly, and renewable.

[0052] The cellulose-based conductive hydrogel of the present invention has the following advantages:

[0053] As mentioned above, the antifreeze performance of cellulose-based hydrogels in the prior art needs to be further improved. Cellulose is difficult to dissolve in general salt solutions. Even if it is dissolved, it is difficult to obtain a cellulose-based hydrogel with high conductivity, good mechanical properties, and higher antifreeze performance. The present invention uses alkalized pretreated cellulose, combined with a specific content of alkalized pretreated cellulose and a metal salt solution (containing the above-mentioned zinc salt, lithium salt and water) The ratio, as well as the composition of the metal salt solution, obtains a cellulose-based hydrogel that meets the sensing and 3D printing performance, and has better antifreeze performance, and has both high conductivity and good mechanical properties, and has achieved unexpected technical effects.

[0054] On the basis of the above advantages, the cellulose-based conductive hydrogel of the present invention also has the following characteristics:

[0055] The storage modulus (G') and loss modulus (G") are analyzed. As the shear force increases, the storage modulus of the cellulose-based hydrogel of the present invention is basically smaller than the loss modulus, indicating that it is more inclined to the state of a viscoelastic liquid. It also shows that the cellulose-based hydrogel has the property of being able to transform from a shear-thinning fluid to a solid-like state during the printing process, so it can maintain good shape fidelity, indicating that the cellulose-based hydrogel prepared by the present invention meets good 3D printing performance;

[0056] The conductivity of the cellulose-based conductive hydrogel of the present invention is 6-7.5 S / m, and the conductivity of most hydrogels is generally lower than 1 S / m, which indicates that free ions exist in the cellulose-based conductive hydrogel system prepared by dissolving cellulose in a metal salt solvent system, and can move in the three-dimensional network system of the cellulose-based conductive hydrogel, providing ion carriers for the conduction of the cellulose-based hydrogel, and effectively improving the conductivity of the cellulose-based conductive hydrogel;

[0057] The cellulose-based conductive hydrogel cut into thin slices was fixed on the fingers, wrists and arms of the human body, and an electrochemical workstation was used to collect the changes in electrochemical signals when these parts were periodically bent. When the parts of the human body changed periodically, the rate of change of the current passing through the hydrogel also showed periodic changes over time, which indicated that the cellulose-based conductive hydrogel had good sensing properties and could be used in sensors, especially wearable flexible electronic devices, to monitor human movement and health. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 This is a scanning electron microscope image of the cellulose not pretreated used in Comparative Example 1 at a magnification of 100 times;

[0059] Figure 2 Scanning electron microscope image of the cellulose pretreated by alkalization in Example 1 at a magnification of 100 times.

[0060] Figure 3 It is a curve diagram of the antifreeze performance of the cellulose-based conductive hydrogel in Examples 1-4 at -80°C to 20°C detected by differential scanning calorimetry.

[0061] FIG4(a) is a graph showing the variation of the current over time when the hydrogel sheet in Example 1 is attached to a finger of a human body and the finger is bent regularly;

[0062] FIG4( b ) is a graph showing the change of the current over time when the hydrogel sheet in Example 1 is attached to the wrist of a human body and the wrist is bent regularly;

[0063] FIG4(c) is a graph showing the change of the current over time when the hydrogel sheet in Example 1 is attached to a human arm and the arm is bent regularly. DETAILED DESCRIPTION

[0064] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0065] The following raw materials:

[0066] Cotton pulp cellulose was purchased from Xinxiang Chemical Fiber Co., Ltd.

[0067] Unless otherwise specified, the devices in the following embodiments are all commercially available conventional devices in the art.

[0068] Unless otherwise specified, room temperature in the following examples refers to 25°C.

[0069] In the following examples and comparative examples, the molar ratio of zinc salt to lithium salt is based on the molar amount of zinc element and lithium element respectively; the molar ratio of the total amount of metal salt to deionized water is also based on the total molar amount of zinc element and lithium element.

[0070] Example 1

[0071] Preparation method of cellulose-based hydrogel:

[0072] Step 1: Na2CO3 and deionized water are prepared into an alkaline solution at a mass ratio of 1:20, and then cotton pulp cellulose is added. The amount of the alkaline solution is 100 mL relative to 1 g of cellulose. The solution is stirred using a high-speed homogenizer at room temperature (25°C). After stirring for 1 hour, the cellulose is repeatedly rinsed with deionized water until the pH of the cellulose is neutral. The cellulose is then added to a solution of anhydrous ethanol and deionized water in a volume ratio of 3:7, and freeze-dried using a freeze dryer to obtain a pretreated cellulose sample;

[0073] Step 2: prepare a metal salt solution, according to the molar ratio of zinc salt to lithium salt (calculated as the molar amount of metal element) being 1:1, and the molar ratio of the total amount of metal salt (calculated as the molar amount of metal element) to deionized water being 1:3, mix Zn(NO3)2, LiBr, and deionized water, stir at 90°C for 1 hour, and then stir at room temperature for 1 hour to obtain a metal salt solution;

[0074] Step 3: gradually add the alkalized pretreated cellulose to the prepared metal salt solution, the amount of pretreated cellulose added is 5% of the mass of the solvent (i.e., the metal salt solution), the dissolution temperature is 90°C, and the dissolution process is carried out using magnetic stirring for 4 hours to obtain a completely dissolved cellulose-based hydrogel with a transparent and uniform texture.

[0075] 3D printing cellulose-based hydrogels

[0076] Step a: the cellulose-based hydrogel obtained in this example, which is completely dissolved and presents a transparent and uniform texture, is poured into a syringe barrel, and then placed in a centrifuge for degassing treatment at a centrifugal speed of 7000 r / min for 10 min;

[0077] Step b: Place the syringe on the extrusion equipment and debug the injection device;

[0078] Step c: Model the target graphics with CAD, then use Simply 3D slicing software to slice the model and import it into the 3D printer for printing. The 3D printing nozzle moves at a speed of 100 mm / min, and the injection speed of the injection pump is set to 40 uL / min.

[0079] Example 2

[0080] Step 1: Na2CO3 and deionized water are prepared into an alkaline solution at a mass ratio of 1:20, and then cotton pulp cellulose is added. The amount of the alkaline solution is 100 mL relative to 1 g of cellulose. The solution is stirred using a high-speed homogenizer at room temperature (25°C). After stirring for 1 hour, the cellulose is repeatedly rinsed with deionized water until the pH of the cellulose is neutral. The cellulose is then added to a solution of anhydrous ethanol and deionized water in a volume ratio of 3:7, and freeze-dried using a freeze dryer to obtain a pretreated cellulose sample;

[0081] Step 2: prepare a metal salt solution, according to the molar ratio of zinc salt to lithium salt (calculated as the molar amount of metal element) being 1:1, and the molar ratio of the total amount of metal salt (calculated as the molar amount of metal element) to deionized water being 1:3, mix Zn(NO3)2, LiBr, and deionized water, stir at 90°C for 1 hour, and then stir at room temperature for 1 hour to obtain a metal salt solution;

[0082] Step 3: gradually add the alkalized pretreated cellulose to the prepared metal salt solution, the amount of pretreated cellulose added is 4% of the mass of the solvent (i.e., the metal salt solution), the dissolution temperature is 90°C, and the dissolution process is magnetically stirred for 4 hours to obtain a completely dissolved cellulose-based hydrogel with a transparent and uniform texture.

[0083] The method for 3D printing cellulose-based hydrogel is the same as that in Example 1.

[0084] Example 3

[0085] Step 1: Na2CO3 and deionized water are prepared into an alkaline solution at a mass ratio of 1:20, and then cotton pulp cellulose is added. The amount of the alkaline solution is 100 mL relative to 1 g of cellulose. The solution is stirred using a high-speed homogenizer at room temperature (25°C). After stirring for 1 hour, the cellulose is repeatedly rinsed with deionized water until the pH of the cellulose is neutral. The cellulose is then added to a solution of anhydrous ethanol and deionized water in a volume ratio of 3:7, and freeze-dried using a freeze dryer to obtain a pretreated cellulose sample;

[0086] Step 2: prepare a metal salt solution, according to the molar ratio of zinc salt to lithium salt (calculated as the molar amount of metal element) being 1:1, and the molar ratio of the total amount of metal salt (calculated as the molar amount of metal element) to deionized water being 1:3, mix Zn(NO3)2, LiBr, and deionized water, stir at 90°C for 1 hour, and then stir at room temperature for 1 hour to obtain a metal salt solution;

[0087] Step 3: gradually add the alkalized pretreated cellulose to the prepared metal salt solution, the amount of pretreated cellulose added is 3% of the mass of the solvent (i.e., the metal salt solution), the dissolution temperature is 90°C, and the dissolution process is magnetically stirred for 4 hours to obtain a completely dissolved cellulose-based hydrogel with a transparent and uniform texture.

[0088] The method for 3D printing cellulose-based hydrogel is the same as that in Example 1.

[0089] Example 4

[0090] Step 1: Na2CO3 and deionized water are prepared into an alkaline solution at a mass ratio of 1:20, and then cotton pulp cellulose is added. The amount of the alkaline solution is 100 mL relative to 1 g of cellulose. The solution is stirred using a high-speed homogenizer at room temperature (25°C). After stirring for 1 hour, the cellulose is repeatedly rinsed with deionized water until the pH of the cellulose is neutral. The cellulose is then added to a solution of anhydrous ethanol and deionized water in a volume ratio of 3:7, and freeze-dried using a freeze dryer to obtain a pretreated cellulose sample;

[0091] Step 2: preparing zinc salt and lithium salt solutions, according to the molar ratio of zinc salt to lithium salt (based on the molar amount of metal elements) being 1:1, and the molar ratio of the total amount of metal salt (based on the molar amount of metal elements) to deionized water being 1:3, Zn(NO3)2, LiBr, and deionized water are mixed, stirred at 90°C for 1 hour, and then stirred at room temperature for 1 hour to obtain a metal salt solution;

[0092] Step 3: gradually add the alkalized pretreated cellulose to the prepared metal salt solution, the amount of pretreated cellulose added is 2% of the mass of the solvent (i.e., the metal salt solution), the dissolution temperature is 90°C, and the dissolution process is magnetically stirred for 4 hours to obtain a completely dissolved cellulose-based hydrogel with a transparent and uniform texture.

[0093] The method for 3D printing cellulose-based hydrogel is the same as that in Example 1.

[0094] Example 5

[0095] A cellulose-based hydrogel was prepared according to the method in Example 1, except that the molar ratio of zinc salt to lithium salt was 1:1.5.

[0096] The texture of the obtained cellulose-based hydrogel is still relatively uniform and can meet the sensing and 3D printing performance requirements. However, when the cellulose dissolution time is increased to 5 hours, the color of the obtained cellulose-based hydrogel becomes light yellow, indicating that the cellulose is slightly degraded due to the increase in heating time.

[0097] Example 6

[0098] A cellulose-based hydrogel was prepared according to the method in Example 1, except that the molar ratio of zinc salt to lithium salt was 1:0.6.

[0099] The obtained cellulose-based hydrogel has uniform texture and can meet the sensing and 3D printing performance requirements, but compared with Example 1, the strength of the cellulose-based hydrogel is weakened.

[0100] Example 7

[0101] A cellulose-based hydrogel was prepared according to the method in Example 1, except that the dissolution temperature in step 3 was 110°C.

[0102] The obtained cellulose-based hydrogel has a uniform texture and can meet the sensing and 3D printing performance requirements, but the dissolution rate is accelerated. However, the hydrogel appears light yellow after dissolution, indicating that the dissolution temperature is slightly high and cellulose degradation has occurred.

[0103] Example 8

[0104] A cellulose-based hydrogel was prepared according to the method in Example 1, except that NaOH was used instead of Na2CO3 in step 1, and the rest was the same as in Example 1.

[0105] It has been verified that the antifreeze performance, electrical conductivity and mechanical properties of the obtained cellulose-based hydrogel are close to those of Example 1.

[0106] Comparative Example 1

[0107] The cellulose-based hydrogel was prepared according to the method in Example 1, except that step 1 in Example 1 was not performed, that is, the cellulose was not pretreated, and other conditions were the same as in Example 1.

[0108] Under the same other conditions, the amount of cellulose dissolved in Comparative Example 1 is reduced, the difficulty of dissolution is increased, and its tensile strength is lower than that of Example 1. In addition, when the dissolved cellulose content is reduced, the hydrogel is difficult to stack and form, and the 3D printing performance is not met.

[0109] The cellulose before and after alkalinization pretreatment was analyzed by scanning electron microscope. Figure 1 , Figure 2 . Figure 1 This is a scanning electron microscope image of the cellulose not pretreated used in Comparative Example 1 at a magnification of 100 times; Figure 2 Scanning electron microscope image of the cellulose pretreated by alkalization in Example 1 at a magnification of 100 times.

[0110] Depend on Figure 1 , Figure 2 By comparison, it can be seen that the alkalization pretreatment of cellulose can reduce the length and diameter of the cellulose microfibril bundles to a certain extent, and the surface of the cellulose microfibril bundles is damaged to a certain extent, which can refine and shorten the cellulose microfibril bundles. The thinner and shorter the cellulose microfibril bundles are, the easier the cellulose is to dissolve. Therefore, the alkalization pretreatment of cellulose can destroy the dense structure of cellulose, making it easier to dissolve in the metal salt solution of the present invention.

[0111] Comparative Example 2

[0112] The cellulose-based hydrogel was prepared according to the method in Example 1. Only zinc salt was used as the metal salt solution. The strength of the cellulose-based hydrogel was severely weakened, as shown in Table 2. It was difficult to stack and form, and salt precipitation occurred at room temperature (20° C.).

[0113] Comparative Example 3

[0114] The cellulose-based hydrogel was prepared according to the method in Example 1. Only lithium salt was used as the metal salt solution, and cellulose was difficult to dissolve. As the amount of cellulose dissolved decreased, its tensile strength also decreased, as shown in Table 2. Therefore, a cellulose-based hydrogel that met the sensing and 3D printing performance requirements could not be obtained.

[0115] Comparative Example 4

[0116] The cellulose-based hydrogel was prepared according to the method in Example 1, except that the molar ratio of zinc salt to lithium salt in the metal salt solution was 1:0.2. The tensile strength of the dissolved cellulose-based hydrogel was greatly reduced compared with that in Example 1. Stacking simulation using a syringe could not be performed by stacking, and there was no shape fidelity, which did not meet the 3D printing performance requirements.

[0117] Test Example 1

[0118] The cellulose-based hydrogels in Examples 1-8 were tested using the following method:

[0119] The cellulose-based conductive hydrogels prepared in Examples 1-8 were tested for rheological properties using a steady-state rheometer to determine their printability at room temperature (25°C). In steady-state mode, the shear rate was set to 0-100s, and the viscosity of the ink was measured as a function of the shear rate. At the same time, the cellulose-based conductive hydrogels in the examples were subjected to a strain scan of 0.01-100% at a fixed frequency of 1Hz to analyze the changes in viscosity as a function of shear rate, storage modulus (G') and loss modulus (G"). The storage modulus (G') and loss modulus (G") were analyzed. As the shear force increased, the storage modulus of the cellulose-based hydrogel was basically smaller than the loss modulus, indicating that it was more inclined to the state of a viscoelastic liquid. It also showed that the cellulose-based hydrogel had the property of being able to transform from a shear-thinning fluid to a solid-like state during the printing process, so it could maintain good shape fidelity, indicating that the cellulose-based hydrogel prepared by the present invention met good 3D printing performance.

[0120] Test Example 2

[0121] Differential scanning calorimetry was used to detect the antifreeze properties of the cellulose-based conductive hydrogels in Examples 1-4 at -80°C. The temperature change was controlled to explore the relationship between the heat flow between the sample and the reference as the temperature changed. A differential scanning calorimeter was used to examine whether the hydrogel had crystallization behavior at low temperatures, and to explore the antifreeze properties of the cellulose-based conductive hydrogel. The present invention uses a differential scanning calorimeter to test the glass transition temperature of the cellulose-based conductive hydrogel. The sample mass is 5-10 mg, the test temperature is -80 to 20°C, the heating rate is 10°C / min, and N2 atmosphere protection is used. See the results. Figure 3 .

[0122] pass Figure 3 It was found that within the range of -80°C to 20°C, the curves of the cellulose-based conductive hydrogels in Examples 1-4 all tended to be stable, and no crystallization peak appeared, indicating that the cellulose-based conductive hydrogel did not freeze within this temperature range. This shows that the prepared cellulose-based conductive hydrogel has relatively excellent antifreeze properties and can still maintain stable performance at lower temperatures (-80 to -20°C).

[0123] Similarly, it has been verified that the cellulose-based conductive hydrogels in Examples 5-8 also have relatively excellent antifreeze properties and can still maintain stable performance at relatively low temperatures (as low as -80°C, such as -78°C, -76°C, -75°C and above).

[0124] Test Example 3

[0125] The conductivity of the cellulose-based hydrogel in the examples was tested by the following method: the cellulose-based conductive hydrogel in Examples 1-4 (the conductivity sample was 10 mm*10 mm*2 mm) was tested for conductivity at room temperature using a four-probe tester to measure its conductivity. The tensile strength of the cellulose-based conductive hydrogel at room temperature (25° C.) was tested using an electronic universal testing machine (the tensile strength test sample was 65 mm in length and 35 mm in gauge length), and the results are shown in Table 1.

[0126] Table 1

[0127] project Tensile Strength Conductivity S / m Example 1 1.3MPa 6.2672 Example 2 0.8MPa 6.3699 Example 3 0.5MPa 6.5219 Example 4 0.4MPa 7.4486 Example 5 1.6MPa - Example 6 0.3MPa - Comparative Example 2 0.1MPa - Comparative Example 3 0.1MPa - Comparative Example 4 0.2MPa -

[0128] It can be seen from Comparative Example 1 that when cellulose is not subjected to the pretreatment of the present invention, even if the same metal salt solution as in Example 1 of the present invention is used, the amount of cellulose dissolved in Comparative Example 1 is reduced, the difficulty of dissolution is increased, and its tensile strength is lower than that of Example 1. In addition, when the dissolved cellulose content is reduced, the hydrogel is difficult to stack and form, and the 3D printing performance is not met.

[0129] In Comparative Example 2, only zinc salt was used in the metal salt solution, and the strength of the obtained cellulose-based hydrogel was severely weakened, making it difficult to stack and form, and the 3D printing performance was not met.

[0130] In Comparative Example 3, the metal salt solution only uses lithium salt, and cellulose is difficult to dissolve. As the amount of cellulose dissolved decreases, its tensile strength also decreases, and a cellulose-based hydrogel that meets the sensing and 3D printing performance requirements cannot be obtained.

[0131] Although zinc salt and lithium salt are used in the metal salt solution in Comparative Example 4, the ratio of zinc salt to lithium salt is not within the scope of the present invention. The tensile strength of the cellulose-based hydrogel after dissolution is greatly reduced compared with that in Example 1. Stacking simulation using a syringe cannot be performed by stacking, and there is no shape fidelity, which does not meet the 3D printing performance.

[0132] For the cellulose-based hydrogels in Comparative Examples 1-4, since they all failed to meet the 3D printing performance, their conductivity was not tested.

[0133] It can be seen from the embodiments of the present invention and the above comparative examples that only by adopting the pretreatment step of the present invention to cellulose can a cellulose-based hydrogel with better performance be obtained by the method of the present invention; only a metal salt solution in which zinc salt and lithium salt act together can construct a cellulose-based hydrogel with uniform texture and better performance.

[0134] It can be seen from the embodiments of the present invention that the present invention uses alkali-pretreated cellulose, combined with a specific content of alkali-pretreated cellulose and a ratio of a metal salt solution, as well as the composition of the metal salt solution, to obtain a cellulose-based hydrogel that meets the sensing and 3D printing performance requirements, achieving unexpected technical effects.

[0135] Furthermore, it can be seen from Table 1 that the conductivity of the cellulose-based conductive hydrogel of the present invention is 6-7.5 S / m, while the conductivity of most hydrogels in the prior art is generally lower than 1 S / m. It can be seen that the cellulose-based conductive hydrogel of the present invention has a better conductivity. This indicates that there are free ions (such as Br) in the cellulose-based conductive hydrogel system prepared by dissolving cellulose using the metal salt solvent system of the present invention. - The free ions can move in the three-dimensional network system of the cellulose-based conductive hydrogel, providing ion carriers for the conductivity of the cellulose-based hydrogel, and effectively improving the conductivity of the cellulose-based conductive hydrogel.

[0136] It can be seen from Examples 1-6 in Table 1 that under the same solvent conditions, the tensile strength of the cellulose-based hydrogel increases with the increase of the cellulose content. Under the same cellulose content conditions, the tensile strength of the cellulose-based hydrogel increases with the increase of the lithium salt content. It can be seen from Example 5 that although the tensile strength of the cellulose-based hydrogel increases with the increase of the lithium salt content, when the lithium salt content increases and the zinc salt content decreases, the difficulty of cellulose dissolution increases. Therefore, preferably, the molar ratio of zinc salt to lithium salt is more preferably 1: (0.8-1.2). Within this preferred range, the tensile strength of the cellulose-based hydrogel is higher, and the dissolution process of cellulose is easier to control. It has been verified that the conductivity of the cellulose-based hydrogels of Examples 5 and 6 is close to that of Example 1, wherein the conductivity in Example 5 is slightly lower than that in Example 1, about 6.1S / m, and the conductivity of the cellulose-based hydrogel in Example 6 is slightly higher than that in Example 1.

[0137] It can be seen from Examples 1-4 that the conductivity of the cellulose-based hydrogel obtained in Example 4 is higher than that in Examples 1-3. When the cellulose content is reduced, the conductivity of the cellulose-based hydrogel increases, but its tensile strength decreases compared with Examples 1-3, indicating that the cellulose content of Examples 1-3 increases and the three-dimensional network structure of the hydrogel is denser. More preferably, the content of the cellulose pretreated by alkali is 3%-5% of the mass of the solvent (i.e., the metal salt solution), and further more preferably 4%-5%. The obtained cellulose-based hydrogel has both high strength and excellent conductivity.

[0138] Combining Test Examples 2 and 3, it can be seen that the cellulose-based hydrogel of the present invention overcomes the disadvantage of being not frost-resistant in the prior art and has excellent antifreeze performance. On the basis of having excellent antifreeze performance, the cellulose-based hydrogel of the present invention also has good electrical conductivity and mechanical properties, achieving unexpected technical effects.

[0139] Test Example 4

[0140] The hydrogel in Example 1 was cut into thin sheets of 10 mm × 20 mm × 2 mm, and attached to the fingers, wrists, arms and other parts of the human body. The fingers, wrists and arms were bent regularly, and the change of current over time during the process was detected by an electrochemical workstation. The voltage was 3 V and the sensitivity (A / V) was 0.01. The sensing performance of cellulose-based conductive hydrogel was studied. The results are shown in Figures 4(a), 4(b) and 4(c).

[0141] As can be seen from Figure 4(a), Figure 4(b), and Figure 4(c), when the body parts undergo periodic changes, the rate of change of the current passing through the hydrogel also shows periodic changes over time, which indicates that the cellulose-based conductive hydrogel has good sensing properties and can be used in sensors, especially wearable flexible electronic devices, to monitor human movement and health.

[0142] Similarly, it has been verified that the cellulose-based conductive hydrogels in Examples 1-8 also have good sensing properties and can be used in sensors.

[0143] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0144] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0145] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0146] The endpoints and any values ​​of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0147] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

[0148] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.

Claims

1. A cellulose-based hydrogel comprising a zinc salt, a lithium salt, water and alkalized pretreated cellulose; In the cellulose-based hydrogel, based on the total mass of zinc salt, lithium salt and water as 100%, the content of the alkalized pretreated cellulose is 1%-6%, the molar ratio of the total amount of zinc salt and lithium salt to water is 1:(3-4), the molar ratio of zinc salt to lithium salt is 1:(0.4-2.4), and the molar amounts of zinc salt and lithium salt are both calculated based on the content of zinc element and lithium element.

2. The cellulose-based hydrogel according to claim 1, characterized in that: In the cellulose-based hydrogel, the content of the alkalized pretreated cellulose is 2%-5%, more preferably 3%-5%, based on the total mass of the zinc salt, the lithium salt and the water as 100%; and / or The molar ratio of the total amount of zinc salt and lithium salt to water is 1:(3-3.5); and / or, The molar ratio of zinc salt to lithium salt is 1:(0.6-1.5), preferably 1:(0.8-1.2); and / or, The zinc salt is selected from at least one of Zn(NO3)2, ZnBr2, and ZnSO4; and / or, The lithium salt is selected from at least one of LiBr, LiCl, and Li2SO4.

3. The cellulose-based hydrogel according to claim 1 or 2, characterized in that The preparation method of the alkalized pretreated cellulose comprises: The cellulose is alkalized in an alkali solution, washed to neutrality, dissolved in a mixed solvent, and freeze-dried to obtain alkalized pretreated cellulose.

4. The cellulose-based hydrogel according to claim 3, characterized in that: In the method for preparing the alkalized pretreated cellulose: The cellulose is selected from at least one of cotton pulp cellulose, hemp fiber, and lignin fiber; and / or, The base in the alkaline solution is selected from at least one of a weak base and a strong base, preferably the weak base is selected from at least one of Na2CO3 and K2CO3, and preferably the strong base is selected from at least one of KOH and NaOH; and / or, the mass ratio of alkali to water in the alkaline solution is 1:(15-25); and / or, The amount of the alkaline solution used is 80-120 mL relative to 1 g of cellulose.

5. The cellulose-based hydrogel according to claim 3, characterized in that: In the method for preparing the alkalized pretreated cellulose: The conditions of the alkalization treatment include: a temperature of 20-30° C. and a time of 1-3 h, and / or, the pretreatment is carried out under mixing conditions, preferably using a high-speed homogenizer for stirring; and / or, The method of washing to neutrality is: repeatedly washing the cellulose obtained after pretreatment with water until it becomes neutral; and / or, The mixed solvent is a mixed solution of alcohol and water, and preferably the alcohol is selected from at least one of anhydrous ethanol and propylene glycol; and / or the volume ratio of alcohol to water is (2:8) to (4:6).

6. A method for preparing the cellulose-based hydrogel according to any one of claims 1 to 5, comprising: The alkalized pretreated cellulose is dissolved in an aqueous solution containing zinc salt and lithium salt to obtain a cellulose-based hydrogel.

7. The preparation method according to claim 6, characterized in that: Based on the total mass of zinc salt, lithium salt and water as 100%, the amount of the alkalized pretreated cellulose is 1%-6%, preferably 2%-5%, more preferably 3%-5%; and / or, In aqueous solutions containing zinc and lithium salts: The molar ratio of the total amount of zinc salt and lithium salt to water is 1:(3-4), preferably 1:(3-3.5); and / or, the molar ratio of zinc salt to lithium salt is 1:(0.4-2.4), preferably 1:(0.6-1.5), more preferably 1:(0.8-1.2), the molar amounts of zinc salt and lithium salt are both calculated based on the content of zinc element and lithium element; and / or, The zinc salt is selected from at least one of Zn(NO3)2, ZnBr2, and ZnSO4; and / or, The lithium salt is selected from at least one of LiBr, LiCl, and Li2SO4.

8. The preparation method according to claim 6, characterized in that: The dissolution conditions include: a temperature of 90-120°C, and / or a time of 3-5 hours; preferably, a temperature of 90-100°C, and / or a time of 3-4 hours; and / or, The preparation method further comprises: After dissolving the alkalized pretreated cellulose in an aqueous solution containing zinc salt and lithium salt to obtain a cellulose-based hydrogel, the cellulose-based hydrogel is injected into a container and then subjected to a degassing treatment. Preferably, the container is placed in a centrifuge for degassing.

9. Application of the cellulose-based hydrogel according to any one of claims 1 to 5 or the cellulose-based hydrogel prepared by the preparation method according to any one of claims 6 to 8 in the fields of 3D printing, flexible sensors, and wearable electronic devices.

10. The use according to claim 9, characterized in that: When the cellulose-based hydrogel is used for 3D printing, the moving speed of the 3D printing nozzle is 80-130 mm / min; and / or the injection speed of the injection pump containing the cellulose-based hydrogel is 30-60 uL / min.

Citation Information

Patent Citations

  • Preparation method of cellulose conducting hydrogel for 3D printing

    CN109942838A

  • Cellulose-based temperature-sensitive conductive hydrogel, and preparation method and application thereof

    CN108641099A

  • Method for enhancing anti-freeze and tensile properties of cellulose ion hydrogel, anti-freeze stretchable cellulose ion hydrogel and application

    CN110041538A

  • Preparation method of cellulose-based hydrogel with high capacitance performance

    CN111710537A

  • Anti-freezing self-repairing conductive hydrogel and preparation method thereof and flexible sensor

    CN112608508A